2022
DOI: 10.1038/s41598-022-14866-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation and reproductive isolation in the Hetaerina americana species complex

Abstract: Incomplete premating barriers in closely related species may result in reproductive interference. This process has different fitness consequences and can lead to three scenarios: niche segregation, sexual exclusion, or reproductive character displacement. In morphologically cryptic species, isolation barriers can be difficult to recognize. Here, we analyzed the morphological, behavioral, and genetic differences between two sympatric cryptic species of the genus Hetaerina to determine the characters that contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(83 reference statements)
2
3
0
Order By: Relevance
“…This indicates that gene flow is null among the three taxa even when there is co-occurrence at some localities (e.g., EF, Za, Ve, CC, NR; Figure 1). Furthermore, we found that H. calverti is the most divergent taxon and that, in agreement with previous findings (Vega-Sánchez et al, 2022), it…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This indicates that gene flow is null among the three taxa even when there is co-occurrence at some localities (e.g., EF, Za, Ve, CC, NR; Figure 1). Furthermore, we found that H. calverti is the most divergent taxon and that, in agreement with previous findings (Vega-Sánchez et al, 2022), it…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that gene flow is null among the three taxa even when there is co‐occurrence at some localities (e.g., EF, Za, Ve, CC, NR; Figure 1). Furthermore, we found that H. calverti is the most divergent taxon and that, in agreement with previous findings (Vega‐Sánchez et al., 2022), it shows complete genetic isolation from the other two. In contrast, the two groups of H. americana (North and South) showed evidence of a lower degree of divergence; however, the patterns of genetic differentiation allowed us to recognize them as two discrete taxa, except for two populations (EF and SN) that showed some mixed ancestry, which can be associated to incomplete or weaker isolation barriers between these two taxa, as are ecological barriers (Sánchez‐Guillén et al., 2012).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations